Radiological Evaluation of Inferior Turbinate in Patients with Deviated Nasal Septum using Computed Tomography (Nepalese Journal of Radiology, 2020)
Introduction: Compensatory hypertrophy of inferior turbinate in the contralateral side of the deviated nasal septum is a known phenomenon. The objective of this study was to establish the relationship between the nasal septum and inferior turbinate and to determine the dimension and composition of inferior turbinate hypertrophy.Methods: This prospective, cross-sectional study was performed on 52 patients who were referred for Computed tomography of PNS with deviated nasal septum having compensatory hypertrophy of contralateral inferior turbinate. Non-hypertrophied inferior turbinate on the side of deviation was taken as a control group. Deviation angle, mucosal thickness including medial and lateral and bone thickness were evaluated using three-dimensional CT scan and compared to the control group.Result: Dimensions of the bony and mucosal components of the inferior turbinate were significantly greater than those of the control group. This study included 52 patients (M- 30, F- 22) having a mean age of 37 years. Out of 52, the septum deviated to the left side in 56% and 44% to the right side. The average angle of deviation was 10.12°. There was a statistically significant correlation (p